Measuring full cost accessibility by auto - Mengying Cui; David Levinson (Journal of Transport and Land Use)
Traditionally accessibility has been analyzed from the perspective of the mean or expected travel time, which fails to capture the full cost, especially the external cost, of travel. The full cost accessibility (FCA) framework, proposed by Cui and Levinson (2018), provides a theoretical basis to fill the gap. It combines temporal, monetary, and non-monetary internal and external travel costs into accessibility evaluations, considering the time cost, crash cost, emission cost, and monetary cost. This paper extends the FCA framework and measures the full cost accessibility by auto for the Minneapolis - St. Paul Metropolitan area, demonstrating the practicality of the FCA framework on real networks.